2014
DOI: 10.1208/s12248-014-9635-2
|View full text |Cite
|
Sign up to set email alerts
|

Induction of Death Receptor CD95 and Co-stimulatory Molecules CD80 and CD86 by Meningococcal Capsular Polysaccharide-Loaded Vaccine Nanoparticles

Abstract: ABSTRACT. Neisseria meningitidis is a leading cause of bacterial meningitis and sepsis, and its capsular polysaccharides (CPS) are a major virulence factor in meningococcal infections and form the basis for serogroup designation and protective vaccines. We formulated a novel nanovaccine containing meningococcal CPS as an antigen encapsulated in albumin-based nanoparticles (NPs) that does not require chemical conjugation to a protein carrier. These nanoparticles are taken up by antigen-presenting cells and act … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
22
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 38 publications
0
22
0
Order By: Relevance
“…The recent advances in the field of nanotechnology facilitated the development of novel meningococcal vaccine formulation that mimics conjugation effects by encapsulation into albumin-based nanoparticle matrices. 8,13,14 The spherical shaped micro and nanoparticles are biological mimics of N. meningitidis bacteria, therefore present to immune system as invader but without the ability to cause disease. The novel meningococcal vaccine nanoparticles formulation encapsulates meningococcal CPS polymers in a biodegradable material that slowly release antigens, therefore enhance antigen presentation by exerting antigen depot effect.…”
Section: The Potential For Novel Meningococcal Vaccine Formulationsmentioning
confidence: 99%
See 2 more Smart Citations
“…The recent advances in the field of nanotechnology facilitated the development of novel meningococcal vaccine formulation that mimics conjugation effects by encapsulation into albumin-based nanoparticle matrices. 8,13,14 The spherical shaped micro and nanoparticles are biological mimics of N. meningitidis bacteria, therefore present to immune system as invader but without the ability to cause disease. The novel meningococcal vaccine nanoparticles formulation encapsulates meningococcal CPS polymers in a biodegradable material that slowly release antigens, therefore enhance antigen presentation by exerting antigen depot effect.…”
Section: The Potential For Novel Meningococcal Vaccine Formulationsmentioning
confidence: 99%
“…The antigenicity of meningococcal vaccine delivered in nanoparticles is significantly higher when compared to vaccine delivered in solution. 13 In addition, the antigenicity of meningococcal vaccine nanoparticles formulation is greatly enhanced when combined with adjuvants like Alum or MF59 also encapsulated in nanoparticles. 8 These adjuvants are approved by Federal and Drug Administration (FDA) to be used with licensed vaccines.…”
Section: The Potential For Novel Meningococcal Vaccine Formulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…These include peptide amphiphile micelles [9], pH responsive polymer-based nanoparticles [10], cationic liposomes [11], polysaccharide-based nanoparticles [12], and nanoparticles formed from biodegradable polymers such as p o l y l a c t i c -c o -g l y c o l i d e ( P L G A ) [ 1 3 -1 5 ] and polyanhydrides [16]. This theme issue includes a comprehensive review by Jewell and colleagues on the topic of harnessing biomaterials to engineer the lymph node microenvironment for immunity or tolerance [17].…”
mentioning
confidence: 99%
“…It was also shown that this vaccine strategy did not induce autoimmunity. D'Souza and colleagues report on the induction of death receptor CD95 and co-stimulatory molecules CD80 and CD86 by meningococcal capsular polysaccharide-loaded vaccine nanoparticles [12]. Neisseria meningitidis is the primary cause of bacterial meningitis and sepsis worldwide, and virulence is mostly dependent on capsular polysaccharides (CPS) that define at least 12 serogroups and are an attractive target for protective vaccines.…”
mentioning
confidence: 99%